1973
DOI: 10.1099/00221287-74-1-77
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Measuring Chemotaxis and Use of the Method to Determine Optimum Conditions for Chemotaxis by Escherichia coli

Abstract: Chemotaxis of a bacterium such as Escherichia coli is assayed by measuring the number of organisms attracted into a capillary tube containing an attractant. Rate of bacterial accumulation in capillaries and a concentration-response curve for L-aspartate taxis are presented and interpreted, and the effect of bacterial concentration is reported. Other parameters of the assay were studied, such as the volume of fluid in the capillary and the size of the capillary opening. The concentration gradient of chemical wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
469
2
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 765 publications
(500 citation statements)
references
References 5 publications
17
469
2
2
Order By: Relevance
“…The continuous-flow capillary assay is based on the traditional quantitative capillary assay developed by Adler (2,3) and modifications thereof (7,38,51,53). In the traditional assay, a capillary filled with chemoattractant dissolved in buffer is placed into a pool of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous-flow capillary assay is based on the traditional quantitative capillary assay developed by Adler (2,3) and modifications thereof (7,38,51,53). In the traditional assay, a capillary filled with chemoattractant dissolved in buffer is placed into a pool of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous-flow capillary assay is a modification of the traditional capillary assay (2,3). Instead of a capillary placed into a stagnant pool of bacteria, a bacterial suspension flows past the open end of a capillary that is perpendicular to the flow path.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two examples are the stopped flow diffusion chamber (SFDC) assay [19][20][21][22] and the capillary assay [1]. Both systems consist of a step-like chemoattractant concentration profile as the initial condition.…”
Section: Examplementioning
confidence: 99%
“…In particular, Rivero et al [33] demonstrated that the individual cellular properties in the Segel's 1-D model could be incorporated into the macroscopic transport parameters. A number of experimental systems (e.g., the capillary assay [1], the stopped-flow diffusion chamber [19,20], and the Boyden chamber [6]) have been designed to generate an attractant concentration gradient in one spatial dimension. Although the measurable macroscopic variable (e.g., the spatial local cell density) in those systems only varies one-dimensionally, microscopically, cells swim freely in 3-D space.…”
Section: Introductionmentioning
confidence: 99%